Determining Audit Report Delays in Property and Real Estate Companies - Putri, Meriska Berliana; Alam, Muhammad Dimar (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to analyze the effect of auditor switching, audit tenure, audit fee, frequency of audit committee meetings, and company size on Audit Report Lag in property and real estate sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. This study is relevant because high Audit Report Lag can affect the relevance of financial reports for corporate decision making. The research data were obtained from annual reports and financial reports available on the official website and company website. A total of 42 companies were selected using a purposive sampling method based on certain criteria. Data analysis was carried out using multiple linear regression methods with the help of Eviews software. The results of the study indicate that auditor switching and audit fees have a significant positive effect on Audit Report Lag, while audit tenure and company size have a significant negative effect on Audit Report Lag. The frequency of audit committee meetings does not show a significant effect. The regression model used explains that variations in Audit Report Lag can be explained by the independent variables analyzed. These findings provide empirical evidence of the consistency of the influence of certain variables on Audit Report Lag as well as practical recommendations for management to optimize the audit process and financial reporting.